Post Implementation Assessment of Social and Environmental Effects of Metro Projects: A Case of Mumbai Metro Line 1 - Saisha Naik; Shomit Bade (Calibrating Urban Livability in the Global South, 2024)
Rapidly increasing urbanization and the need for faster transportation, combined with the limited land supply, necessitates the provision of Mass Rapid Transit Systems like metro projects. These projects have Environmental Impact Assessments and Social Impact Assessments conducted for them and their mitigation plans are in place. There is a need to assess the effectiveness of these mitigation plans and check for other effects post-implementation. This study takes into consideration the Mumbai Metro One and the effects that it has had on the population in its immediate surrounding as well as the city in terms of environmental and social factors. This is done by collecting relevant data through primary surveys, reports and geo-spatial mapping and analyzing it to understand the benefits and issues of the observed due to this project. The gathered data for this study has led to the inference that while benefits are observed on a macro level, on a neighborhood level multiple issues such as traffic congestions and increase in air and noise pollution have been experienced. The study concludes with putting forth a model framework to assess post implementation effects of metro projects that is easy to use and gives recommendations based on the issues observed in this case. This model framework presented in the study shall enable a concise evaluation of both social and environmental effects of a large project and provide a versatile tool for assessment and analysis.